PERTUMBUHAN DAN HASIL TANAMAN BAYAM PADA BERBAGAI WAKTU PENYIRAMAN - Syaiful Anwar; Nindya Arini; Wahid Nur Fajri (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2026)
Water management is a crucial factor in optimizing the productivity of leafy vegetables, including green spinach (Amaranthus sp.), particularly under limited water availability. Appropriate timing of irrigation may influence plant growth dynamics and biomass allocation. The study aimed to evaluate different irrigation times on the growth and biomass distribution of green spinach. The study was using a single factor with a completely randomized design, namely irrigation time, consisting of three treatments: morning irrigation (07:00), afternoon irrigation (16:00), and a combination of morning and afternoon irrigation (07:00 and 16:00). The treatment was replicated six times, resulting in 18 experimental units. Irrigation volume was standardized based on field capacity. Growth variables observed involved plant height, stem diameter, and number of leaves, while production variables consisted of fresh and dry weights of shoots and roots, as well as the shoot-to-root ratio. Data were analyzed using analysis of variance, with by the Honestly Significant Difference (HSD) test at a 5% significance level. The irrigation timing significantly affected plant height, number of leaves, and shoot-to-root ratio, but had no significant effect on stem diameter or total fresh and dry biomass. Morning irrigation produced a higher shoot-to-root ratio, indicating more efficient biomass allocation to the edible parts of the plant. In conclusion, morning irrigation is recommended as a practical water management strategy to support vegetatif growth and improve resource use efficiency in green spinach cultivation.